MOBILE PHONE INFORMATION CAMPAIGN IN MEDIA AS AN ALTERNATIVE PD.CHRISTIAN CELULER APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Rita Puspita; Cut Asiana Gemawaty, SKom, MMSi (Jurnal Sistem Informasi, 2003)
In the writing of this scientific information discussed regarding the design of mobilephones as an alternative to media campaigns on PD. Christian Cell Phones. Thewriter tries to design a scheme of the information described using OrganizationalStructure, Algorithm, and Program Structure Database Structure-added data that hasbeen programmed using Visual Basic transaction which consists of data menu hp, hpand Carta use menu.Hopefully, with this application program can be made easier PD. Christian Cell inprocessing the data much better than the way of more advanced technology.